Using the whole brain to develop thinking and problem-solving: TASC - thinking actively in a social context - (:unkn) unknown (Nova Science Publishers, Inc., 2014)
In this chapter, I reflect on the generic processes of problem-solving and thinkingskills that, I maintain, should underlie the teaching-learning interactions of all educational intentions; with particular reference to primary, secondary, tertiary and adult education. The chapter proposes a problem-solving framework that could serve as a base for systematic curriculum development that actively promotes thinking and problem-solving. © 2014 Nova Science Publishers, Inc. All rights reserved.